Pengaruh Citarasa Pada Roti Gembong Gembul Terhadap Keputusan Pembelian Konsumen - Agustin, Elrica Sopiani; Rahmadhika, Alda (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
Gembong Gembul Bread, a typical snack from East Kalimantan, offers a soft texture with a unique appearance and various flavor and topping variants. The research was conducted through field methods with a quantitative approach, using questionnaires and statistical tests. The results showed that the taste of Gembong Gembul Bread has a positive influence on consumer purchasing decisions, although the level of relationship between the two variables is relatively low. The majority of consumers choose this product after seeing it directly in the store or based on recommendations from friends or social media. However, there are other factors that also influence consumer purchasing decisions by 88.9% which were not investigated in this study. Therefore, further research is needed to understand other factors that also influence consumer purchasing decisions more comprehensively